Study On The Prevalence Of Pulmonary Tuberculosis Among Hiv Positive Attending Hiv Clinics In Eastern Nepal - Yadav, DK; Jha, N; Pokharel, PK; Niraula, SR; Bhattacharya, SK; Nagesh, S (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2012)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. More than 2 billion people are infected with TB bacilli worldwide. It is a leading public health problem particularly in the developing countries. The HIV epidemic has increased the global tuberculosis burden. TB is the commonest opportunistic infection and leading cause of mortality of People living with HIV (PLHA). Tuberculosis is a major public health problem in Nepal. The objective of the study is to determine prevalence of Pulmonary Tuberculosis among HIV positives attending HIV clinics in Eastern Nepal, and to assess the socio-demographic factors associated with TB and HIV/AIDS. Methodology: Cross-sectional prospective study was carried out among HIV positive attending different VCT and HIV clinics from Sunsari Morang and Jhapa district of Eastern Nepal. Face to face interview was performed and sputum sample were collected using convenience sampling technique. Data was collected from PLHA on related information on Socio-demographic profi le, risk taking behavior with the help of pretested semi-structured questionnaire. Univariate and bivariate analysis were performed using SPSS 15.0. Chi-squire test was performed to establish statistical signifi cance between dependent and independent variables. Results: Out of total 242 PLHA, 75.2% were males and 24.8% females; around half of them (48.8%) were in the age group of (30-39) yrs, 23% in (25-29) yrs, and 15.7% in (20-24) years. Prevalence of pulmonary tuberculosis was found to be 27.3% (n=66). PTB was high among IDU’s (48.6%), followed by clients of CSWs (21%), housewife (13.6%), highway truck drivers (10.6%) and CSWs (6%). Conclusion: Prevalence of PTB is very high among PLHA attending VCT & HIV clinics of Eastern Nepal. This study reveals that PTB is signifi cantly associated with increasing age, risk taking behavior and place of residence. There is urgent need of active case fi nding as well as periodic screening among people living with HIV/AIDS of this region to address HIV-associated TB morbidity and mortality. DOI: http://dx.doi.org/10.3126/saarctb.v8i1.5885 SAARCTB 2011; 8(1): 1-8